Survival Analysis of Pediatric Wilms Tumor Based on Risk Identification - Andy Andy; Yacobda Sigumonrong (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Wilms Tumor (WT) or nephroblastoma is the most common primary malignant tumor of the kidney found in children (comprising about > 95% of all kidney tumors). The study of WT prognostic factors has not been elaborated enough in Indonesia. This study aimed to determine the prognostic factors of WT patients in Adam Malik Hospital, Medan. Methods: This study was conducted with a retrospective design due to the rarity of WT cases. A total of 21 WT patients diagnosed from 2003 to 2019 were taken from medical records at Adam Malik Hospital, Medan. Univariate and multivariate Cox regression analyses were performed to determine the independent prognostic factors of WT. The primary endpoint of this study was patients’ overall survival (OS) obtained by the Kaplan-Meier analysis on significant variables. Results: From the univariate Cox regression analysis, gender was found to be the sole significant factor (HR = 0.218, p = 0.005) where males have a lower hazard ratio. The multivariate Cox regression analysis yielded an age of diagnosis (HR = 13.860, p = 0.014) and complete tumor removals (HR = 0.056, p = 0.008). The Kaplan-Meier analysis was performed on three significant variables mentioned before. Only gender yielded a significant Mantel-Cox log-rank score (p = 0.002) with male patients found to have better survivability with a median survival of 476 days compared to that of females of 11 days. The three-year survival of males was 45.45% while all females did not survive until the cut-off. Conclusions: Three prognostic factors, including children’s gender, age of diagnosis, and tumor removal status, were confirmed to be prognostic factors for the overall survival of children with WT. Further studies covering broader demographic areas were suggested to confirm significant results.